Factors associated with participation in an ongoing national catch-up campaign against rubella: a cross-sectional internet survey among 1680 adult men in Japan - Ai Hori; Shiho Yoshii; Yukari Isaka; Koji Wada (BMC, 2021)
Abstract Background Since 2019, aiming to eliminate periodic rubella outbreaks, the Japanese government has provided a rubella immunization program targeting men born in fiscal years 1972 to 1978, who lacked the opportunity to be vaccinated against rubella in childhood. This study aimed to explore the factors associated with participation in the rubella vaccination program among the first-year target population in 2019. Methods A total of 11,754 adult men in Japan born in fiscal years 1972 to1978 living in seven rubella epidemic areas (Tokyo, Chiba, Kanagawa, Saitama, Aichi, Osaka, and Fukuoka) were selected from a list of a survey agency and invited to complete an Internet questionnaire in March 2020. Recruitment ended when the participants reached 1680 individuals. Multivariable log binomial regression analyses were performed to explore the association between awareness of rubella prevention and rubella antibody testing in fiscal year 2019, adjusting for social characteristics. Results Of the 1680 men aged 41-47 years who completed the survey, approximately half (51.3%) said that they had received a voucher for the rubella antibody testing and vaccination program. One-quarter (25.9%) of the respondents had used the voucher for rubella antibody testing in 2019, and 6.0% had used the voucher for rubella vaccination in fiscal year 2019. Respondents who understood the government recommendation for rubella antibody testing and vaccination for men of their generation (odds ratio [OR]: 5.50; 95% confidence interval [CI]: 4.01-7.53), those with acquaintances who had undergone rubella testing (OR: 1.39; 95% CI: 1.22-1.59), and those who knew that about their lack of opportunity for rubella vaccination (OR: 1.33; 95% CI: 1.11-1.60) tended to undergo rubella antibody testing. Receiving the most recent seasonal influenza vaccination (OR: 1.26; 95% CI: 1.10-1.43) and being able to confirm a rubella vaccination history (OR: 1.28; 95% CI: 1.13-1.46) were also associated with rubella antibody testing. Conclusions The ongoing Japanese test-and-vaccinate rubella program has yet to achieve its participation rate goal for 2019. Further dissemination of the government recommendation to the population is necessary, along with improvements in the accessibility of the rubella vaccination program.